Remote Outcomes of Sclerotherapy with Ethanol in Hydrocele Patients - Z.A. , Kadyrov; O.B. , Zhukov; R.Kh. , Olimov; M.V. , Faniev; N.V. , Demin (International Journal of Psychosocial Rehabilitation, 2020)
Introduction. Conventional methods of treating hydrocele are rather traumatic and seem unsatisfying to both doctors and patients; therefore, their improvement is needed. The objective of this study is to evaluate the efficiency and safety of sclerotherapy of hydrocele with 96% ethanol. Patients: 117 patients aged from 35 to 89, with hydrocele volume over 100 ml, were divided into three groups: 34 patients who received sclerotherapy by the studied method, 25 patients who received conventional sclerotherapy, and 58 patients who received a widely adopted surgery. The improved sclerotherapy included 30–40 min exposure to ethanol, subsequent evacuation of ethanol from the scrotum, and repeated injection of 5–10 ml of ethanol without evacuation. Results: In Group I, the first sclerotherapy cured 97.1% of patients; in Group II, 72%. During the two months after the therapy, complications were observed in 14.5%, 16%, and 62.2% of patients, respectively. In Group I, 24 patients assessed tolerability as excellent and 10 patients as good. In Group II, only 13 patients assessed tolerability as excellent, while 8 patients marked it as poor. In Group III, 20 patients assessed tolerability as excellent and 16 patients as poor. The spermatogenesis rate was 8.7±0.5 before and 8.6±0.4 after the sclerotherapy (Johnsen scale modified by De Kretser and Holstein). The testicle volume on the hydrocele side was 20.9±1.5 cm³ after sclerotherapy, compared to 25.2±2.2 cm³ prior to it. The linear blood flow velocity in parenchyma arteries was 0.104+0.020 m/s before and 0.122+0.024 m/s after the sclerotherapy. The average resistivity index in parenchyma arteries was 0.81±0.05 m/s before and 0.74±0.06 m/s after the sclerotherapy. These average values were found to be statistically reliable (р<0.05). No reliable change in the spermogram was revealed 6 months after the treatment. Conclusions. The improved sclerotherapy with 96% ethanol minimized the hydrocele relapse and reduced early postoperative complications. This method showed no adverse effect upon the testicle tissue; on the contrary, it conduced to better blood supply and lymph efflux from the parenchyma, which can be confirmed by the examination results.